Eksistensi Politik Hukum Li dan Fa Dalam Ajaran Cina - Nana Supena; Taufiqurrohman Syahuri (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
This study examines the existence of Li and Fa in the Chinese legal system and legal politics. This research uses a normative legal methodology based on a historical methodology. According to the findings of the study, the legal system and Chinese legal politics emphasize the terms Li and Fa, which, in essence, allude to Li's teachings, which emphasize a set of ethical or moral standards that regulate patterns of human behavior and must be adhered to by every individual. In the meanwhile, Fa is a written law that every Chinese citizen must respect. In essence, this concept is a law that is intrinsic to the state, applies universally and without exception, and is codified in statutes. These two terms became the standard for the development of China's legal system and legal politics. Indirectly, China, which adheres to communism, follows the standards of morality and the law as a guide for life.